(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Community service is based on the results of an analysis of the complexity of the problems that are owned by BKM Al-Mukhlisin, the congregation of the mosque is dominated by people who need it even though the potential for fundraising still exists, but if this potential is just channeled it will not be able to improve the economy of community around Al-Mukhlisin mosque. The proposed model is a productive waqf model which is expected to be able to maximize the potential for raising funds, especially waqf for use by the surrounding community who need it for productive activities. Based on an analysis of BKM Al-Mukhlisin, it is known that it is necessary to increase productive waqf literacy in accordance with Islamic law for BKM management, especially in the process of organizational development. The community service process uses a participatory dialogue method to explore the needs and culture of BKM Al-Mukhlisin, followed by intense and ongoing training and assistance to BKM. Community service activities focus on improving the organizational structure of BKM Al-Mukhlisin with the theme of productive waqf management training, to achieve the goal of the mosque as a center of worship and an economic center for the community around the mosque